“Modelización espacial de áreas de protección de cauces hídricos en el cantón Quinsaloma, provincia de los ríos” - Cajas Aguilar, Edwin Estalin (2022)
At present, the water bodies lose the degree of importance in their conservation by society and competent authorities according to overexploitation, consumption and contamination in the different agricultural, tourist, electrical and industrial potential activities, consequently, the present investigation has the purpose spatially model protection areas for the watercourses of the Quinsaloma canton with the aim of developing a PGIRH. The proposed methodology indicated that through the application of 90 surveys to society and interviews with the leaders of the precincts related to the study, the citizen's perception of the current water situation of the canton is measured, in addition, a resource management proposal is proposed. based on 4 strategic sectors identified as main sources of contamination. As a result, it was obtained that through citizen perception, agricultural, mining and industrial activities are the sectors with the greatest environmental impact that affect the canton and that water resources do not receive due relevance for their preservation by authorities and society as a whole. However, the interviews with community leaders showed that the main basin for multiple and essential use in the region is the Calabí river, which, according to current climatic conditions, decreases its flow, although it has an extensive area of green soil with Forest crops, perennial and semi perennial. The Comprehensive Water Resources Management Plan proposed strategies and activities framed in the sectors: agricultural, industrial, electrical and tourism, which are a